2005
DOI: 10.1021/om050030g
|View full text |Cite
|
Sign up to set email alerts
|

Third-Order Nonlinear Optical Properties of Some Electron-Rich Iron Mono- and Trinuclear Alkynyl Complexes

Abstract: The syntheses of [1,3,5-{(η 2 -dppe)(η 5 -C 5 Me 5 )FeCtC-4-C 6 H 4 CtC} 3 C 6 H 3 ] (1) and [(η 2 -dppe)-(η 5 -C 5 Me 5 )Fe(CtC-1,4-C 6 H 4 CtCPh)] (2) are reported, together with an X-ray diffraction study of 2. The linear optical spectra of these compounds reveal characteristic low-energy transitions at 430 and 436 nm, respectively, significantly red shifted in comparison to those recorded for [1,3,5-{(η 2 -dppe)(η 5 -C 5 Me 5 )FeCtC} 3 C 6 H 3 ] (3) and [(η 2 -dppe)(η 5 -C 5 Me 5 )FeCtCPh] (4), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
51
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 39 publications
(80 reference statements)
7
51
0
Order By: Relevance
“…[14] These alkyne bonds give rise to two diagnostic 13 C NMR signals at 94.4 and 90.0 ppm, absent in the spectrum of 3-H. A TEM image reveals molecules of 4 deposited on an alumina support with a diameter of around 55 , consistent with that suggested by molecular modeling (see the Experimental Section (Computational Details) and the Supporting Information).…”
supporting
confidence: 70%
See 3 more Smart Citations
“…[14] These alkyne bonds give rise to two diagnostic 13 C NMR signals at 94.4 and 90.0 ppm, absent in the spectrum of 3-H. A TEM image reveals molecules of 4 deposited on an alumina support with a diameter of around 55 , consistent with that suggested by molecular modeling (see the Experimental Section (Computational Details) and the Supporting Information).…”
supporting
confidence: 70%
“…Although the magnitude of the TPA for a given compound originates in part from the match between twice the incoming beam energy and the energy of the TPA excited state, the data are suggestive of significantly higher TPA cross-sections for 3-NO 2 and 4, as previously seen with nitrophenylethynyl complexes or complexes of octupolar symmetry such as 1 a or 1 b. [14,15] Upon mono-oxidation, an increase in the magnitude of g imag and of the TPA cross-section s 2 for the linear complexes is seen. The second oxidation switches the behavior of these compounds from two-photon absorbers to saturable absorbers (the latter corresponding to negative g imag values).…”
supporting
confidence: 55%
See 2 more Smart Citations
“…38a, 80 It has also been shown that modified electron-rich dinuclear acetylide complexes 31 can be grafted onto hydrogenated silicon surfaces and exhibit facile stepwise electron transfer between the bound metal centres and the silicon surface through the interfacial Si-C bond, paving the way to devices.…”
mentioning
confidence: 99%